Environmental Controls of InSAR‐Based Periglacial Ground Dynamics in a Sub‐Arctic Landscape. Issue 7 (20th July 2021) - Rouyet, L.; Karjalainen, O.; Niittynen, P.; Aalto, J.; Luoto, M.; Lauknes, T. R.; Larsen, Y.; Hjort, J.
Abstract: Periglacial environments are characterized by highly dynamic landscapes. Freezing and thawing lead to ground movement, associated with cryoturbation and solifluction. These processes are sensitive to climate change and variably distributed depending on multiple environmental factors. In this study, we used multi‐geometry Sentinel‐1 Synthetic Aperture Radar Interferometry (InSAR) to investigate the spatial distribution of the mean annual ground velocity in a mountainous landscape in Northern Norway. Statistical modeling was employed to examine how periglacial ground velocity is related to environmental variables characterizing the diverse climatic, geomorphic, hydrological and biological conditions within a 148 km 2 study area. Two‐dimensional (2D) InSAR results document mean annual ground velocity up to 15 mm/yr. Vertical and horizontal velocity components in the East–West plane show variable spatial distribution, which can be explained by the characteristics of cryoturbation and solifluction operating differently over flat and sloping terrain. Statistical modeling shows that slope angle and mean annual air temperature variables are the most important environmental factors explaining the distribution of the horizontal and vertical components, respectively. Vegetation and snow cover also have a local influence, interpreted as indicators of the ground material and moisture conditions. The results show contrasted model performance depending on the velocity component used as a response variable. In general, our study highlights the potential of integrating radar remote sensing and statistical modeling to investigate mountainous regions and better understand the relations between environmental factors, periglacial processes and ground dynamics. Plain Language Summary: In cold regions, freeze and thaw cycles lead to movement in the upper part of the ground. The landscape distribution of these movements depends on several environmental conditions, such as the local climate, topography, vegetation, material type and soil moisture. Here we mapped millimeter to centimetre mean annual ground velocities using a measurement technique based on satellite radar images. We analyzed how the environmental conditions are related to the distribution of the ground velocity at the landscape scale. Statistical models were applied to relate the ground velocity to environmental conditions at similar locations and showed that the spatial variability of the air temperature and the slope inclination are the two main controlling factors. Vegetation and snow cover have also an indirect effect due to their link with the ground material and moisture conditions. In general, the study contributes to the development of approaches integrating remote sensing and modeling techniques to cover large and hard‐to‐access mountainous regions and provide new insights on the processes shaping the landscape in cold environments. Key Points: Multi‐geometry Synthetic Aperture Radar Interferometry documents the distribution of the ground velocity in a periglacial environment Coupling remote sensing and statistical modeling provides insights on the environmental controls of the velocity at the landscape scale Topo‐climatic variables are the key factors explaining the ground dynamics associated with cryoturbation and solifluction processes